Peer interactions during storybook reading on children’s knowledge construction: an experimental study on K2 and K3 children - Wu, Xuanyi Eliza; Ko, James (Frontiers in Education, 2024)
This study explored the effects of peer interactions on kindergarten children’s construction of conservation and conflict resolution knowledge during storybook reading. Previous studies have identified that peer interactions can support the meaning-making processes of children in social relationships and problem-solving, but little is known about whether the interaction with mixed-age or more competent peers is more important in supporting knowledge construction. Sixty-four younger children in K2 and older children in K3 with similar socioeconomic backgrounds were recruited from a Montessori kindergarten in Kunming, China. An experimental design was applied to explore age group and conserver dominance effects on conservation and conflict resolution. Children were assigned randomly to eight groups in three 30-to-40-minute intervention sessions. Each session had a different theme for the children to learn about conservation and conflict resolution concepts and a hands-on activity to practice and discuss. ANOVAs were performed to test group effects, while multiple regression analyses were conducted to explore individual variations in age and pre-test scores in predicting post-test scores. Conservation knowledge was significantly better among children who differed in age groups in the post-test, but differences were not found in conflict resolution knowledge. Groups balanced with equal conservers and non-conservers improved the best, suggesting that peer social interactions can facilitate conservation and conflict resolution construction. These results provide new insights for early childhood educators to support peer interactions and children’s development. Implications, limitations, and future research are discussed.